A Tale of Two Schools: A Practitioner’s Use of Bourdieu’s Theory to Understand Academic Underachievement Among Students at His Inner-City School - Brar, Victor S (Journal of the Canadian Association for Curriculum Studies, 2017)
This paper describes my journey, as a teacher at a Canadian inner-city elementary school, toward conceptually understanding why many children at my current school repeatedly academically underachieve. I have utilized Bourdieu’s theory of practice as a heuristic to examine how social reproduction operates differently for school children from different social classes and leads to differences in achievement. The first component of this paper establishes a crucial theoretical base for practitioners by describing theory of practice and its key concepts of cultural capital, habitus, field, and symbolic violence, to explicate how social reproduction functions in education, highlighting the roles of institutions and professionals, and the transformative and generative potentials of Bourdieu’s theory. The second component provides important epistemological and methodological considerations regarding how practitioners might conduct successful empirical studies while avoiding the problems that are prevalent in existing empirical literature.